2020
DOI: 10.1177/1724600820926172
|View full text |Cite
|
Sign up to set email alerts
|

Programmed death-ligand 1 single nucleotide polymorphism affects breast cancer chemosensitivity and adverse events in the neoadjuvant setting

Abstract: Objective We aimed to determine whether single nucleotide polymorphisms in the PD-L1 gene are related to the response and adverse events of patients receiving neoadjuvant therapy and to explore the mechanism. Methods Nine single nucleotide polymorphisms of PD-L1 were selected and tested among patients before neoadjuvant therapy. Four models were used in single nucleotide polymorphism genotype analysis: the addictive model compared TT vs TA vs AA; the dominant model compared TT vs TA+AA; the recessive model com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
(55 reference statements)
0
2
0
2
Order By: Relevance
“…Yeo and his colleagues reported that the PD‐L1 rs4143815 GG genotype may be beneficial for predicting poor prognosis in lung adenocarcinoma as patients with this genotype had lower overall survival and disease-free survival compared to patients with other genotypes of PD-L1 rs4143815 [ 27 ]. As well, prior studies stated that the PD‐L1 rs4143815C > G was significantly associated with a worse survival outcome and relapse with NSCLC and breast cancer [ 10 , 28 , 29 ]. Furthermore, Lee et al [ 30 ] investigated whether the PD-L1 gene polymorphisms could predict the clinical outcome of patients with advanced NSCLC after paclitaxel-cisplatin chemotherapy and they found that the rs4143815 CG SNP was significantly associated with a better response under additive model for the G-allele.…”
Section: Discussionmentioning
confidence: 87%
“…Yeo and his colleagues reported that the PD‐L1 rs4143815 GG genotype may be beneficial for predicting poor prognosis in lung adenocarcinoma as patients with this genotype had lower overall survival and disease-free survival compared to patients with other genotypes of PD-L1 rs4143815 [ 27 ]. As well, prior studies stated that the PD‐L1 rs4143815C > G was significantly associated with a worse survival outcome and relapse with NSCLC and breast cancer [ 10 , 28 , 29 ]. Furthermore, Lee et al [ 30 ] investigated whether the PD-L1 gene polymorphisms could predict the clinical outcome of patients with advanced NSCLC after paclitaxel-cisplatin chemotherapy and they found that the rs4143815 CG SNP was significantly associated with a better response under additive model for the G-allele.…”
Section: Discussionmentioning
confidence: 87%
“…Importantly, TAP1 and HLA-A are essential components of T cell function, and high expression of these molecules was found to increase the survival probability of melanoma patients [23]. Moreover, since miRNA influences PD-L1 expression, immunotherapy with high expression of miR34c therefore results in the downregulation of PD-L1 mRNA expression in breast cancer [24].…”
Section: Discussionmentioning
confidence: 99%
“…Mutações não codificantes de SNPs estão frequentemente associadas ao desenvolvimento de tumores. Atualmente, os estudos de SNPs têm se concentrado principalmente na codificação de SNPs (Lu et al, 2020).…”
Section: Tipos De Polimorfismo Em Pd-l1unclassified
“…Foi observado que, o SNP (rs4143815do) do gene PD-L1 foi associado à taxa de resposta patológica completa, sobrevida livre de doença e eventos adversos em pacientes com câncer de mama recebendo terapia neoadjuvante. Vários ensaios clínicos em larga escala confirmaram que os pacientes que atingem a resposta patológica completa em terapia neoadjuvante têm um prognóstico muito melhor do que pacientes sem resposta patológica completa (Lu et al, 2020).…”
Section: Tipos De Polimorfismo Em Pd-l1unclassified